PERSEPSI GURU TERHADAP PROFESI KEPENDIDIKAN DI KECAMATAN TEBAS - Rudi Permana; Aswandi Aswandi; M. Chiar (Universitas Tanjungpura, 2019)
Abstract This study aims to determine teacher perceptions of the educational profession. The method in this study uses qualitative methods. The results showed that: (1) teachers' perceptions of the task in terms of the selection aspect show that teachers had an opinion on the need to use their knowledge and experience in choosing information related to preparing Lesson Plans; (2) teacher perceptions in terms of organizational aspects show the teacher sees the need to distinguish true information related to education and distinguish between the main tasks of teachers and those that are not appropriate tasks; (3) teacher perceptions in terms of interpretation show that teachers believe the educational profession is a noble profession; (4) teacher perceptions in terms of gender indicate that female teachers have stronger perceptions than male teachers; (5) teachers' perceptions in terms of educational background show that teachers with a Master degree have higher perceptions than teachers with a bachelor degree / Diploma two / High School equivalent; (6) teachers' perceptions in terms of years of service, it was found that teachers who had a tenure of 15 to 24 years had higher perceptions than teachers who had other tenure. Keywords: Teacher's Perceptions, Educational Profession.